Demonstration of soap making from used oil during the community program for raising awareness on open burning - Mohamed, Bebe Norlita; Wondi, Mohd Hafizz; Mohd Khairlani, Nurul Hidayah; Mansur, Nurul Syahirah; Sulaiman, Muhamad Nasarudin (Corporate Communication Unit, UiTM Mukah Campus, 2025)
The main objective of this session was to educate community members on how to convert used cooking oil, commonly discarded after use, into a valuable and eco-friendly household product. The demonstration was well-received and highlighted an innovative way of promoting sustainability through practical, everyday practices.